A new technique to determine the tension in extensor pollicis longus reconstruction. (October 2019) - Kamoi, Fumiki; Kondo, Makoto; Hayashi, Masanori; Uchiyama, Shigeharu; Kato, Hiroyuki
We present an original technique for determining the tension of the extensor pollicis longus tendon after reconstruction. We treated 20 patients using this technique for an extensor pollicis longus tendon graft or extensor indicis tendon transfer and reviewed the results. The tension of the reconstructed extensor pollicis longus was adjusted so that the centre of the distal edge of the thumbnail was elevated 2 cm above the operation table. The mean retropositional distance of the treated thumbs was 1.2 cm less than the contralateral thumbs. The mean total active motion of the thumb was 90%. This technique resulted in satisfactory thumb function. Level of evidence: IV